Hyaluronic acid-based nanofibers: Electrospun synthesis and their medical applications; recent developments and future perspective - Humaira; Raza Bukhari, Sayyad Ali; Shakir, Hafiz Abdullah; Khan, Muhammad; Saeed, Shagufta; Ahmad, Irfan; Muzammil, Khursheed; Franco, Marcelo; Irfan, Muhammad; Li, Kun (Frontiers in Chemistry, 2022)
Hyaluronan (HA) is a biodegradable, biopolymer that represents a major component of the extracellular matrix and has the potential to be fabricated in a fibrous form in combination with other polymers via electrospinning. Unique physicochemical features such as viscoelasticity, conductivity, and biological activity mainly affected by molecular weight attracted the attention of biomedical researchers to utilize hyaluronan for designing novel HA-based nano-devices. Particularly HA-based nanofibers get focused on a diverse range of medical applications such as tissue implants for regeneration of damaged tissue or organ repair, wound dressings, and drug delivery carriers to treat various disorders. Currently, electrospinning represents an effective available method for designing highly porous, 3D, HA-based nanofibers with features similar to that of the extra-cellular matrix making them a promising candidate for designing advanced regenerative medicines. This review highlights the natural sources of HA, recently cited protocols in literature for HA production through fermentation, fabrication of HA-based nanofibers via electrospinning, and recent progress in medical applications of these electrospun HA-based nanofibers